2012
DOI: 10.5194/os-8-633-2012
|View full text |Cite
|
Sign up to set email alerts
|

TOPAZ4: an ocean-sea ice data assimilation system for the North Atlantic and Arctic

Abstract: Abstract. We present a detailed description of TOPAZ4, the latest version of TOPAZ -a coupled ocean-sea ice data assimilation system for the North Atlantic Ocean and Arctic. It is the only operational, large-scale ocean data assimilation system that uses the ensemble Kalman filter. This means that TOPAZ features a time-evolving, state-dependent estimate of the state error covariance. Based on results from the pilot MyOcean reanalysis for 2003-2008, we demonstrate that TOPAZ4 produces a realistic estimate of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
262
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(312 citation statements)
references
References 71 publications
6
262
0
1
Order By: Relevance
“…The sea-ice-ocean model of TOPAZ (hereafter called the TOPAZ model) is used here in free-run mode (i.e., no data assimilation is applied) in the same configuration as in Sakov et al (2012). The model grid covers the Arctic and North Atlantic oceans with a mean resolution of approximately 12 km over the Arctic.…”
Section: Topaz Trajectories Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…The sea-ice-ocean model of TOPAZ (hereafter called the TOPAZ model) is used here in free-run mode (i.e., no data assimilation is applied) in the same configuration as in Sakov et al (2012). The model grid covers the Arctic and North Atlantic oceans with a mean resolution of approximately 12 km over the Arctic.…”
Section: Topaz Trajectories Datasetmentioning
confidence: 99%
“…The TOPAZ model in free-run mode has been evaluated in Sakov et al (2012) and was found to overestimate seaice drift by about 3 km day −1 compared to buoy data. To try to solve this issue, the frictional drag parameters for the atmosphere-ice stress has been reduced to c a = 0.0016 in the TOPAZ operational platform (not yet documented).…”
Section: Topaz Trajectories Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…For the model evaluation we force our model with the ocean state of the TOPAZ4 reanalysis (see Sakov et al, 2012), and with the atmospheric state of the Arctic System Reanalysis, Interim version (ASR-Interim hereafter) (http://rda.ucar. edu/datasets/ds631.4/, Byrd Polar Research Centre/The Ohio State University (2012).…”
Section: Simulation Set-upmentioning
confidence: 99%